Over a million students use our free study notes to help them with their homework
The answer can be found by using the chain rule and simple substitution as well as basic knowledge of differentiation.f’(x)= -6cos(3x)sin(3x)
cos^2(A) + sin^2(A) = 1, sin(A+B) = sinAcosB + cosAsinB, cos(A+B) = cosAcosB - sinAsinB, sin2A = 2sinAcosA (if A = B), cos2A = cos^2(A) - sin^2(A) (if A = B), cos2A = 1 - 2sin^2(A) => sin^2(A) = 1/2(1 ...
This equation can be solved using separation of variables. Firstly we rearrange the equation so that all of the y's are on the left hand side and all of the x's are on the right: 1/y2* dy = 6x ...
(4-8x)^(-3/2) =Factoring out 4^(-3/2) to make binomial expansion easier(1-2x)^(-3/2) =Using the binomial series expansion in the formula booklet, up to the term in x^3<...
3/2x2 -2/5x5/2 +C
←
350
351
352
353
354
→
Internet Safety
Payment Security
Cyber
Essentials